Asset tracking, condition visibility and sustainability using unmanned aerial systems in global logistics. (November 2020) - Sellevold, Ethan; May, Travis; Gangi, Sam; Kulakowski, Jakub; McDonnell, Ian; Hill, Doug; Grabowski, Martha
Abstract: The scale and scope of global logistics systems make real-time visibility of individual assets in global logistics systems difficult. Aggregating global logistics data to a manageable level where interruptions and disruptions can be anticipated or resolved is high on the wish list of global logistics managers and decision makers. Asset tracking and condition visibility in global supply chains is also difficult because few standards or metrics have been assessed in a supply chain, particularly when new technology is introduced, such as unmanned aerial systems in global supply chains. In this paper, we describe the integration of an unmanned aerial system in a global logistics system, and the metrics used to assess the integrated system. We highlight the importance of supply chain process, business impact, societal and environmental sustainability metrics, in addition to economic and supply chain performance metrics, in evaluating the integrated system. Highlights: Unmanned aerial systems in global supply chains offer opportunities to improve asset tracking and condition visibility. Metrics to measure new technology impacts in global logistics systems are proposed. A prototype technology demonstration for infrastructure poor settings highlights important sustainability metrics.